Narrative ecologies : teachers as pedagogical toolmakers - Turvey, Keith (Milton Park, Abingdon, Oxon : Routledge, 2013)
'In recent years there has been significant investment by policy makers in the potential of technological tools to transform learning and teaching across a range of professional practitioner groups; education, nursing and social care. There remain, however, outstanding issues concerning the ways educators and professional practitioners harness the potential of technologies to innovate and develop pedagogical practice. With so much attention focusing on technologies themselves, the complexity of what it takes for practitioners to innovate and develop their own pedagogical practice can easily be overlooked.This book promotes a teacher-centred model of professional development and practice; a model that promotes teachers as active agents as they draw upon a range of factors within a narrative ecology framework to inform their development of pedagogical tools. The combination of narrative methodologies with ecological theories offers a much more nuanced view of teachers' professional learning, and Turvey provides an innovative methodological approach to narrative research, supported by an empirical evidence base which crosses educational and socio-cultural contexts. Chapters cover:-Teachers as pedagogical toolmakers-A teacher-centred narrative ecology-Storying teachers' experiences: what can we learn?The narrative ecologies that emerge in this book suggest an incremental process of pedagogical change and development, driven by teachers at the heart of the process. This book will be key reading for postgraduate students and academics focusing on narrative methodologies and aspects of professional learning within contemporary contexts'--
Includes bibliographical references (pages [149]-156) and index.
Keywords: Teachers -- In-service training; Educational technology